(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The utilisation of electric vehicles (EVs) plays an integral role in the transition toward a more sustainable future in the automotive industry. The purpose of this review is to provide a structured and systematically organised analysis of EVs, focusing on the factors that encourage their usage and how these factors relate to the performance of the vehicles. With this structured overview, this review will improve the understanding of EV fundamentals and shed light on dubious or debated areas. By comparing and examining a range of research papers, this review singles out key correlations and insights to present the most reliable information. Ultimately, it not only enhances the overall understanding of electric vehicles but also offers a promising foundation for future research in this field.